Increased production of nitric oxide correlates with tumor growth in Algerian patients with nasopharyngeal carcinoma - Bourouba, Mehdi; Boukercha, Aziza; Zergoun, Ahmed-Amine; Zebboudj, Abderezak; Elhadjan, Mohamed; Djenaoui, Djamel; Asselah, Fatima; Touil-Boukoffa, Chafia (Biomarkers, 2012)
Nasopharyngeal carcinoma (NPC) is thought to arise because of chronic inflammation. The correlation between nitric oxide (NO) production, a biomarker of inflammation and NPC development remains unexplored. To investigate this question, we performed a profile analysis on plasma collected from untreated, treated, remissive, cured and relapsing patients. Nitrites were measured to assess NO activity. We observed that increased nitrites concentrations in untreated and relapsing patients associated with tumor development. Moreover, nitrites levels were similar in remissive, cured and healthy individuals. Altogether, our results suggest that NO might be an interesting blood biomarker to monitor tumor growth in NPC patients.